Predicting the potential distribution of four endangered holoparasites and their primary hosts in China under climate change - Lu, Xin; Jiang, Ruoyan; Zhang, Guangfu (Frontiers in Plant Science, 2022)
Climate change affects parasitic plants and their hosts on distributions. However, little is known about how parasites and their hosts shift in distribution, and niche overlap in response to global change remains unclear to date. Here, the potential distribution and habitat suitability of four endangered holoparasites and their primary hosts in northern China were predicted using MaxEnt based on occurrence records and bioclimatic variables. The results indicated that (1) Temperature annual range (Bio7) and Precipitation of driest quarter (Bio17) were identified as the common key climatic factors influencing distribution (percentage contribution > 10%) for Cynomorium songaricum vs. Nitraria sibirica (i.e., parasite vs. host); Temperature seasonality (Bio4) and Precipitation of driest month (Bio14) for Boschniakia rossica vs. Alnus mandshurica; Bio4 for Cistanche deserticola vs. Haloxylon ammodendron; Precipitation of warmest quarter (Bio18) for Cistanche mongolica vs. Tamarix ramosissima. Accordingly, different parasite-host pairs share to varying degree the common climatic factors. (2) Currently, these holoparasites had small suitable habitats (i.e., moderately and highly) (0.97–3.77%), with few highly suitable habitats (0.19–0.81%). Under future scenarios, their suitable habitats would change to some extent; their distribution shifts fell into two categories: growing type (Boschniakia rossica and Cistanche mongolica) and fluctuating type (Cynomorium songaricum and Cistanche deserticola). In contrast, the hosts’ current suitable habitats (1.42–13.43%) varied greatly, with highly restricted suitable habitats (0.18–1.00%). Under future scenarios, their suitable habitats presented different trends: growing type (Nitraria sibirica), declining type (Haloxylon ammodendron) and fluctuating type (the other hosts). (3) The niche overlaps between parasites and hosts differed significantly in the future, which can be grouped into two categories: growing type (Boschniakia rossica vs. Alnus mandshurica, Cistanche mongolica vs. Tamarix ramosissima), and fluctuating type (the others). Such niche overlap asynchronies may result in severe spatial limitations of parasites under future climate conditions. Our findings indicate that climate factors restricting parasites and hosts’ distributions, niche overlaps between them, together with parasitic species identity, may jointly influence the suitable habitats of parasitic plants. Therefore, it is necessary to take into account the threatened holoparasites themselves in conjunction with their suitable habitats and the parasite-host association when developing conservation planning in the future.